ABO Blood Group Type and the Risks of Peripheral Artery Disease in Type II Diabetes Mellitus - Pratama, Dedy; Puruboyo, Adi N.D (UI Scholars Hub, 2023)
Introduction. Peripheral artery disease (PAD) is a common complication of diabetes mellitus (DM), affecting up to 20% of people over 65. Blood type is hypothesized to influence PAD, although it has yet to be extensively studied. We aim to investigate the correlation between ABO blood group type and the severity of PAD in patients with type II DM. Methods. We conducted a cross-sectional study on DM type II patients with PAD at the Cipto Mangunkusumo National Hospital in Indonesia between January 2022 to June 2022. PAD was diagnosed based on the ankle-brachial index (ABI) measurement. The PAD severity was grouped into mild (ABI 0.7-0.9) and moderate-severe (ABI <0.7). Patients were categorized as O blood type and non-O (A, B, and AB). Results. Of 366 patients included, 194 with O type and 172 with non-O type. No significant difference in the occurrence. PAD was significantly more severe in non-O blood type patients (p = 0.041). Longer periods of diabetes (OR 10.325, CI95% 5.108-20.871, p <0.001) and hypertension (OR 4.531, CI95% 1.665-12.326, p <0.003) were risk factors for more severe PAD. Conclusion. ABO blood group type was not significantly associated with the occurrence of PAD in patients with type II DM. Non-O blood type was associated with more severe PAD, while more prolonged periods of diabetes and hypertension were found to be significant risk factors for more severe PAD.